Artificial Intelligence and its Implications in Higher Education - Ocaña-Fernández, Yolvi (2019)
The new challenges of the information society demand from the university a severe change in its rigid canons of education. The artificial intelligence-based formats promise a very substantial improvement in education for all the different levels, with an unprecedented qualitative improvement: to provide the students with an accurate personalization of their learning according to their requirements, managing to integrate the different forms of human interaction and information and communications technologies. The great challenge of the university of the new millennium lies in the urgent need to plan, design, develop and implement digital skills in order to train better professionals capable of understanding and developing the technological environment according to their needs, as well as implementing the universalization of a digital language supported by programs developed under artificial intelligence formats.